Effects of Nicotine and Tobacco-Related Products on the Feeding Behavior of the German Cockroach (Blattodea: Blattellidae). Issue 2 (4th March 2021) - Di Ilio, Vincenzo; Birkett, Michael A; Pickett, John A
Abstract: Animals use olfaction to detect developmentally significant volatile organic compounds (VOCs) in their local environment. As part of a wider study aiming to demonstrate that the olfactory responses of animals to VOCs can be modified through the creation of a drug-addicted status and association with a selected VOC, we investigated nicotine and tobacco smoke particulate (TSP) extract as possible addictive compounds for male German cockroaches, Blattella germanica (Linnaeus). In feeding experiments using an artificial food stimulus, food treated with TSP extract was preferred over untreated food. Surprisingly, nicotine, which was expected to be the most important addictive tobacco component, did not induce noticeable effects on cockroach behavior. Both TSP extract and nicotine were shown to be phagostimulants. Olfactometry assays that measured odor-mediated insect behavior demonstrated that male B. germanica did not choose TSP-extract-treated food even when attempts were made specifically to train them via this modality. These results support a hypothesis that B. germanica needs to consume TSP-containing food to show a clear preference for this stimulus and that gustatory mechanisms are involved due to compounds present in the TSP extract.